Experimental study of quaternary blends with diesel/palm-oil biodiesel/ethanol/diethyl ether for optimum performance and emissions in a light-duty diesel engine using response surface methodology - Ooi, Jong Boon; Chan, Xian Loong; Jaliliantabar, Farzad; Tan, Boon Thong; Wang, Xin; Song, Cher Pin; Chiong, Meng-Choung; Hung, Yew Mun (Elsevier, 2024)
Quaternary fuel blend consisting of diesel, palm-oil biodiesel (POB), diethyl ether (DEE), and ethanol is a promising low-carbon fuel solution for diesel engines. In this study, the effects of DEE, ethanol, and engine load on the brake specific fuel consumption (BSFC), nitrogen oxides (NOx), carbon monoxide (CO), and unburned hydrocarbons (UHCs) emissions of a light-duty diesel engine were statistically analyzed using analysis of variance (ANOVA). Desirability-based response surface methodology (RSM) optimization was then employed to determine the optimum quaternary fuel blend. The desired optimum quaternary fuel blend was found to be 6.78 vol% DEE and 20.00 vol% ethanol at an operating engine load and speed of 31.36 % and 2000 rpm, respectively. The engine out responses of BSFC and NOx, CO, and UHCs emissions for the optimal solution were 490.58 g/kWh, 326.84 ppm, 0.300 vol%, and 156.95 ppm, respectively. Validation of the optimized parameters was conducted through actual engine experiments and the errors were less than 5 %. The results suggest that the optimum quaternary blend can be a cleaner alternative for light-duty diesel engine applications.